Reconstruction of Tax Judges' Ratio Decidendi in International Tax Disputes based on The Principle of Substance Over Form - Sri Wisnuaji; Muchlas Rowi (Asian Journal of Social and Humanities, 2026)
This research examines the weaknesses in tax judges’ ratio decidendi in resolving international tax disputes, which remain dominated by a formalistic approach. Problems arise when legal considerations rely more on the legal form of a transaction than on its underlying economic substance, potentially leading to inconsistent decisions and legal uncertainty. This study analyzes judges’ reasoning patterns in Tax Court decisions, particularly when addressing the complexity of cross-border transactions. This research uses normative legal methods, including statutory, case-based, conceptual, and comparative approaches. It relies on the principle of substance over form, which has developed in international practice through the OECD and the Base Erosion and Profit Shifting initiative. The results reveal inconsistencies in the application of ratio decidendi and the limited use of the principle of substance over form in judges’ legal reasoning. This condition results in weak harmonization with global standards and has the potential to create injustice for taxpayers. This research offers a reconstruction of the tax judges’ reasoning model that grounds ratio decidendi in economic substance without neglecting the legal certainty derived from written norms. This model is expected to improve decision consistency, strengthen the legitimacy of tax justice, and support the integration of national tax law with international developments.